Two novel TNB energetic cocrystals with low melting point: a potential strategy to construct melt cast explosive carriers. Issue 16 (6th April 2022) - Qiao, Shen; Wang, Jianhua; Yu, Yanwu; Liu, Yucun; Yang, Zongwei; Li, Hongzhen
Abstract : Two novel low melting-point cocrystals with high performances were obtained by cocrystallizing TNB with 1, 4-DNI and DNMT, namely TNB/1, 4-DNI (1 ) and TNB/DNMT (2 ). Abstract : Two novel low melting point cocrystals were obtained by cocrystallizing TNB (1, 3, 5-trinitrobenzene) with 1, 4-DNI (1, 4-dinitrimidazole) and DNMT (1-methyl-3, 5-dinitro-1, 2, 4-triazole), respectively. Cocrystal TNB/1, 4-DNI (1 ) and TNB/DNMT (2 ) both belong to the orthorhombic system with a 1 : 1 ratio. Compared with the pure TNB, both cocrystals have low melting points ( T m < 90 °C) and better predicted detonation properties ( D > 7700 m s −1 ). Most notably, cocrystal 1 shows an ability to reform the cocrystal again after melting and cooling, which makes it possible to be used as a new type of melt-cast explosive carrier to replace TNT (2, 4, 6-trinitrotoluene). Thus, cocrystallization provides a potential strategy to construct the new melt-cast explosive carriers in the future.